2020
DOI: 10.1029/2019wr026750
|View full text |Cite
|
Sign up to set email alerts
|

Diversion of Flow and Sediment Toward a Side Channel Separated From a River by a Longitudinal Training Dam

Abstract: A human-made entrance to a side channel separated from the river by a longitudinal training dam can be considered a new, emergent type of river bifurcation. To understand the processes controlling the diversion of flow and sediment toward the side channel at such bifurcations, a comprehensive field monitoring program was performed in the Waal River, which is the main branch of the Rhine River in the Netherlands. Local processes govern the flow field in the bifurcation region. The angle between the main river f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The 50th ( D 50 ) and 90th percentile sediment diameter ( D 90 ) were determined following the approach of de Ruijsscher et al. (2020a) and are shown in Figure 1 ( bs 1 through bs 5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 50th ( D 50 ) and 90th percentile sediment diameter ( D 90 ) were determined following the approach of de Ruijsscher et al. (2020a) and are shown in Figure 1 ( bs 1 through bs 5).…”
Section: Methodsmentioning
confidence: 99%
“…The RWS data were acquired with an interval of six days, on October 9 and October 15. At the location of the field site, information on the bed grain size distribution is also available, based on samples that have been taken on November 24, 2017 using a Hamon grab (de Ruijsscher et al, 2020b;Eleftheriou & Moore, 2013). The 50th (D 50 ) and 90th percentile sediment diameter (D 90 ) were determined following the approach of de Ruijsscher et al (2020a) and are shown in Figure 1…”
Section: Field Campaignmentioning
confidence: 99%
“…These LTDs are river training structures 3-4 km long parallel to the river's shoreline that divide the river into a main channel (230 m wide) and shore channels (80 m) protected from the effects of navigation on river banks and biodiversity (Eerden, 2013;Collas et al, 2018). One of the LTD shore channels was estimated to carry 18-27% of the total river discharge (De Ruijsscher et al, 2020). These structures were constructed with boulders, have an inflow with adjustable boulder sills that are generally fully submerged and an outflow into the main channel of the river.…”
Section: Introductionmentioning
confidence: 99%
“…They also serve as key elements in the restoration of pristine multithread patterns, as in the case of the Drau River in Austria (Figure 1c), where a former side‐channel was reopened with the aim of improving the habitat conditions, stabilize the river bed, and ensure flood protection through channel widening (Formann et al., 2007; Habersack & Piégay, 2007). A further example comes from a novel interest of river restoration practices, namely the construction of the so‐called longitudinal training dams to mitigate the effects of shipping on riverine habitat biodiversity and functionality and, at the same time, guarantee the fluvial navigation (Collas et al., 2018; de Ruijsscher et al., 2020) (Figure 1d).…”
Section: Introductionmentioning
confidence: 99%
“…comes from a novel interest of river restoration practices, namely the construction of the so-called longitudinal training dams to mitigate the effects of shipping on riverine habitat biodiversity and functionality and, at the same time, guarantee the fluvial navigation (Collas et al, 2018;de Ruijsscher et al, 2020) (Figure 1d).…”
mentioning
confidence: 99%